Effectiveness and Safety of Oro-Dispersible Sildenafil in a New Film Formulation for the Treatment of Erectile Dysfunction: Comparison Between Sildenafil 100-mg Film-Coated Tablet and 75-mg Oro-Dispersible Film. Issue 12 (16th November 2017) - Cocci, Andrea; Capece, Marco; Cito, Gianmartin; Russo, Giorgio Ivan; Falcone, Marco; Timpano, Massimiliano; Rizzo, Michele; Della Camera, Pier Andrea; Morselli, Simone; Campi, Riccardo; Sessa, Francesco; Cacciamani, Giovanni; et al.
Abstract: Background: A new oro-dispersible film (ODF) formulation of sildenafil has been developed for the treatment of erectile dysfunction (ED) to overcome the drawbacks that some patients experience when taking the conventional film-coated tablet (FCT). Aim: To assess the effectiveness and safety of sildenafil ODF formulation in patients with ED who were using the conventional FCT. Methods: From May 2017 through July 2017, 139 patients with ED were enrolled. Data from penile color-duplex ultrasound, medical history, hormonal evaluation, and patient self-administered questionnaires were collected. All patients were administered sildenafil 100-mg FCT for 4 weeks. Thereafter, they underwent a 2-week washout period and subsequently took sildenafil 75-mg ODF for 4 weeks. Outcomes: The International Index of Erectile Function (IIEF-15), Hospital Anxiety and Depression Scale (HADS), Patient Global Impressions of Improvement (PGI-I), and Clinician Global Impressions of Improvement (CGI-I) questionnaires were administered and severity of ED was classified as severe (IIEF-15 score ≤ 10), moderate (IIEF-15 score 11–16), or mild (IIEF-15 score = 17–25). Results: All patients completed the final protocol. Differences in mean IIEF scores for erectile function, orgasmic function, sexual desire, and intercourse satisfaction were significantly in favor of sildenafil 100-mg FCT, whereas the mean score for overall satisfaction was in favor of sildenafil 75-mg ODF. A significant difference in changes in HADS score was found from washout to final follow-up (mean difference = −0.19; P < .01). For the ODF formulation, the median CGI-I score was 3.5 (interquartile range [IQR] = 2.5–4.5) and the median PGI-I score was 3.0 (IQR = 2.0–4.0). The median action time was 20.0 minutes (IQR = 15.0–30.0) and the median mouth time was 60.0 seconds (IQR = 30.0–120.0). Clinical Implications: The ODF formulation of a widely known drug, with the same safety and effectiveness of the FCT, was better appreciated by patients in overall satisfaction. Strengths and Limitations: This is the first clinical trial to assess the efficacy of a new formulation of sildenafil in patients with ED. The limitations of the study are related to the methodology used: it was not a case-control study and the patients were not drug-naïve for ED treatment. Therefore, only the "additional" side effects of the ODF formulation compared with FCT are reported. Conclusion: The new ODF formulation is as efficient and safe as the FCT formulation and offers a new choice of treatment to specialists for more precisely tailored therapy.